Melestarikan Tradisi Mancing Ngarong: Harmoni Hukum dan Pariwisata di Teluk Mata Ikan - Tan, Sebastian; Tampubolon, Theresia; Hakim, Teja Maulana; Afifa, Zaynulia; Olivia, Devrina; Disemadi, Hari Sutra (Journal of Judicial Review, 2025)
Local cultural heritage is a Traditional Cultural Expression, which is an important asset and needs to be protected to ensure the continuity and diversity of human cultural heritage. However, this practice is considered to face serious threats due to the rapid development of the modern tourism industry and minimal attention to the preservation of traditional culture. This research will clearly illustrate the urgency of legal protection and preservation of the Ngarong Fishing Culture as an inseparable part of the local cultural heritage which is rich in traditional values. This research uses empirical juridical research with statutory, conceptual and ethnographic approaches. The research stages consist of problem formulation, data collection, data analysis, correlation discovery, preparation of recommendations and preparation of research outputs. The data sources used are primary and secondary data with qualitative descriptive analysis techniques. The research results show that the Ngarong Fishing Culture is not just an ordinary fishing activity, but rather a ritual passed down from generation to generation by the local community. One of the main obstacles in efforts to preserve the Ngarong Fishing Culture in Teluk Mata Ikan Village is that there is no recognition as a Communal Intellectual Property Right at the Directorate General of Intellectual Property (DJKI), so there is a large potential for loss due to intellectual property violations. Therefore, legal protection is needed, interpreted as an effort to protect legal subjects by using positive law which is enforced by its implementers and given sanctions for violators. In traditional expression, this can be done with preventive protection efforts or prevention efforts by registering communal intellectual property rights with the Directorate General of Intellectual Property (DJKI) by the Regional Government with local traditional stakeholders.